Preparation method of micron-sized calcium carbonate based on composite dispersant system

By using a composite dispersant system in the calcium carbonate preparation process, the carbonization reaction is coordinated to regulate the carbonization reaction, and the problems of wide particle size distribution and poor dispersion in the existing technology are solved, and the efficient preparation of monodispersed and single-crystal micron-scale calcium carbonate is achieved, which is suitable for a variety of materials applications.

CN120172443APending Publication Date: 2025-06-20TSINGHUA UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510340082.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

In the existing calcium carbonate preparation process, the particle size distribution is wide, the dispersion is poor, and the crystal shape is complex, making it difficult to achieve efficient preparation of micron-scale calcium carbonate.

Method used

The composite dispersant system is adopted, including sodium hexametaphosphate, sodium tripolyphosphate, EDTA, sucrose and stearic acid. Through the synergistic effect of multiple components, power plant flue gas is added to the calcium carbide slag-ammonia-ammonium chloride system to regulate the carbonization reaction, and the preparation of monodispersed and single-crystalline micron-scale calcium carbonate is realized.

Benefits of technology

It has achieved the preparation of monodispersed and single crystal micron-scale calcium carbonate, with uniform particle size and good dispersion, and is suitable for plastic toughening fillers, biomedical materials or electronic packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of micron-sized calcium carbonate based on a composite dispersant system. The preparation method comprises the following steps: S1, mixing carbide slag with an ammonium chloride solution for calcium extraction reaction to obtain a calcium chloride-ammonia-ammonium chloride solution; s2, adding a solution of a composite additive into the solution obtained in S1, and introducing CO2-containing power plant flue gas for carbonization until the pH value is 7.5-8.5; and S3, carrying out solid-liquid separation, washing and drying on the carbonized product obtained in S2 to obtain the monodisperse micron-sized calcium carbonate. According to the method disclosed by the invention, mono-dispersed and single-crystal micron-sized calcium carbonate with uniform particle size distribution can be obtained; the composite additive is added into a calcium chloride-ammonia-ammonium chloride-power plant flue gas carbonization system, so that the preparation of monodisperse and single crystal type micron-sized calcium carbonate can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of micron calcium carbonate preparation, and in particular to a method for preparing micron-sized calcium carbonate based on a composite dispersant system. Background Art

[0002] In traditional calcium carbonate preparation processes, the selection of crystal form control agents and dispersants plays a decisive role in the morphology, particle size, and dispersibility of the products. In the prior art, a single dispersant (such as sodium hexametaphosphate) easily leads to particle agglomeration, while surface modifiers such as stearic acid need to be added at specific reaction stages to optimize performance. In addition, in specific reaction systems, such as the reaction system of carbide slag and ammonium chloride, there are metal ion impurities such as NH4 + , Cl - , NH3 molecules, Mg 2+ , Fe 2+ etc. that will interfere with the growth of calcium carbonate crystals, making the crystal form of calcium carbonate products complex and the particle size non-uniform. Aiming at the problems of wide particle size distribution and poor dispersibility of the products in the prior art, the present invention is expected to provide a composite additive system to achieve the efficient preparation of micron-sized calcium carbonate through the synergistic effect of multiple components. Summary of the Invention

[0003] The purpose of the present invention is to provide a method for preparing micron-sized calcium carbonate. Using carbide slag - ammonia - ammonium chloride as the calcium source system and power plant flue gas as the carbonization gas source, a single-dispersed and single-crystalline micron-sized calcium carbonate is prepared by adding a composite additive - sucrose, sodium hexametaphosphate, sodium tripolyphosphate, stearic acid, and EDTA to regulate the carbonization reaction in one pot.

[0004] The method for preparing micron-sized calcium carbonate based on a composite dispersant system provided by the present invention includes the following steps:

[0005] S1. Mix carbide slag with ammonium chloride solution for calcium extraction reaction to obtain a calcium chloride - ammonia - ammonium chloride solution;

[0006] S2. Add the solution of the composite additive to the solution obtained in step S1, and introduce power plant flue gas containing CO2 for carbonization until the pH is 7.5 - 8.5;

[0007] The composite additive is a complex of a dispersant, a chelating agent, an auxiliary stabilizer, and a surface modifier;

[0008] S3. Perform solid-liquid separation, washing, and drying on the carbonization product obtained in step S2 to obtain single-dispersed micron-sized calcium carbonate.

[0009] In the preparation method of the present invention, the composite additive is a complex of sodium hexametaphosphate, sodium tripolyphosphate, EDTA, sucrose, and fatty acid;

[0010] The fatty acid may be stearic acid, oleic acid, palmitic acid, etc.;

[0011] Preferably, in the solution of the composite additive, the mass percentage content of each component is as follows:

[0012] Sodium hexametaphosphate 0.5%-1.5%; Sodium tripolyphosphate 0.3%-1.0%; EDTA 0.1%-0.3%; Sucrose 3%-5%; Fatty acid 1%-3%.

[0013] More preferably, the mass percentage content of each component is as follows:

[0014] Sodium hexametaphosphate 0.5%-1.0%, Sodium tripolyphosphate 0.4%-0.5%, EDTA 0.1%-0.2%, Sucrose 4%, Fatty acid 1.5%-3%.

[0015] In the preparation method of the present invention, the mass ratio of the carbide slag (dry basis) to ammonium chloride is 1:1.5-2, and the mass fraction of ammonium chloride in the ammonium chloride solution is 4%-10%.

[0016] In the preparation method of the present invention, the addition amount of the solution of the composite additive is 10%-15% of the mass of the calcium chloride-ammonia-ammonium chloride solution.

[0017] In the preparation method of the present invention, the volume concentration of CO2 in the power plant flue gas is 5%-15%, and the following pretreatment standards are met:

[0018] Dust concentration ≤ 10mg / m 3 , SO2 concentration ≤ 35mg / m 3 , NOx concentration ≤ 50mg / m 3 , Ringelmann blackness ≤ Grade 1.

[0019] In the preparation method of the present invention, the carbonization temperature is 25-35°C;

[0020] The solid-liquid separation is carried out by centrifugal separation, and the centrifugal force is 15000-30000g; the chloride ion content of the washed product ≤ 200ppm.

[0021] The micron-sized calcium carbonate prepared by the method of the present invention has a crystal form of single calcite type, a morphology of spherical-like, and an average particle size of 3-5 microns, and can be used as a plastic toughening filler, a biomedical material or an electronic packaging material.

[0022] Compared with the prior art, the present invention has at least the following effects:

[0023] By adding a composite additive to the carbonization system of calcium chloride - ammonia - ammonium chloride - power plant flue gas, the preparation of monodisperse, single - crystal micron - sized calcium carbonate can be achieved. Through the synergistic effect of sodium hexametaphosphate and sodium tripolyphosphate, the agglomeration of calcium carbonate particles is inhibited by electrostatic repulsion and steric hindrance. Sucrose is used as an auxiliary dispersant to enhance the stability of the system through hydrogen bonding. EDTA preferentially chelates impurity ions such as Fe 3+ , Mg 2+ and other impurity ions in the reaction system to avoid growth defects in calcium carbonate crystals. Stearic acid forms a hydrophobic layer by binding to calcium ions on the surface of calcium carbonate, enhancing the dispersibility of calcium carbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 FIG. is the flow chart for the preparation of micron - sized calcium carbonate based on a composite dispersant system prepared in Example 1 of the present invention;

[0025] Figure 2 FIG. is the scanning electron microscope image of micron - sized calcium carbonate based on a composite dispersant system prepared in Example 1 of the present invention;

[0026] Figure 3 FIG. is the particle size distribution diagram of micron - sized calcium carbonate based on a composite dispersant system prepared in Example 1 of the present invention;

[0027] Figure 4 FIG. is the XRD pattern of micron - sized calcium carbonate based on a composite dispersant system prepared in Example 1 of the present invention;

[0028] Figure 5 FIG. is the particle size distribution of the calcium carbonate product prepared in Comparative Example 1 of the present invention;

[0029] Figure 6 FIG. is the electron microscope image of the calcium carbonate product prepared in Comparative Example 1 of the present invention;

[0030] Figure 7 FIG. is the XRD pattern of the calcium carbonate product prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0031] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0032] Unless otherwise specified, the materials, reagents, etc. used in the following examples can all be obtained from commercial sources.

[0033] The power plant flue gas in the following examples is the purified flue gas after dust removal, desulfurization, and denitrification, with a dust concentration ≤ 10 mg / m 3 , SO2 concentration ≤ 35 mg / m 3 , NOx concentration ≤ 50 mg / m 3 , and Ringelmann blackness ≤ 1 level.

[0034] According to Figure 1 the process shown below, prepare micron-sized calcium carbonate.

[0035] Example 1,

[0036] The carbide slag is taken from the wet carbide slag of a factory in Inner Mongolia, and its composition is shown in Table 1.

[0037] Prepare 5 kg of 10% ammonium chloride solution, add 348 g of carbide slag with a water content of 4.2%, stir at room temperature for 1 h for calcium extraction reaction, filter, and obtain 5.15 kg of calcium chloride-ammonia-ammonium chloride solution.

[0038] Prepare 772.5 g of composite additive solution, among which, 3.86 g of sodium hexametaphosphate, accounting for 0.5 wt%, 3.09 g of sodium tripolyphosphate, accounting for 0.4%, 0.77 g of EDTA, accounting for 0.1%, 30.9 g of sucrose, accounting for 4%, 11.6 g of stearic acid, accounting for 1.5%, and 722 g of water.

[0039] Add the prepared composite additive solution to the obtained calcium chloride-ammonia-ammonium chloride solution. The addition amount of the composite additive solution is 15% of the mass of the calcium chloride-ammonia-ammonium chloride solution. Mix evenly, control the temperature at 30 °C, and introduce the purified flue gas from the power plant after dust removal, desulfurization and denitrification with a CO2 content of 12% until the solution pH = 8.

[0040] Centrifuge the obtained slurry at a centrifugal force of 20000 g, continue to wash the obtained centrifugal filter cake, filter, the chloride ion content in the filter cake is 50 ppm, put it in an oven and dry it at 105 °C to constant weight, and pass through a 100-mesh sieve.

[0041] The scanning electron microscope image of the calcium carbonate prepared in this example is as Figure 2 shown. It can be seen that the calcium carbonate is evenly dispersed and the particle size distribution is uniform.

[0042] The particle size distribution diagram of the calcium carbonate prepared in this example is as Figure 3 shown. It can be seen that the average particle size of the calcium carbonate is 3.2 microns.

[0043] The XRD pattern of the calcium carbonate prepared in this example is as Figure 4 shown. It can be seen that the crystal form of the calcium carbonate is a single calcite type.

[0044] Table 1 Composition content of wet carbide slag (dry basis)

[0045]

[0046]

[0047] Example 2,

[0048] The carbide slag was taken from a dry-process carbide slag in Ningxia, and its composition is shown in Table 2.

[0049] Prepare 5 kg of 6% ammonium chloride solution, add 150 g of carbide slag, and stir at room temperature for 0.5 h for calcium extraction reaction. After filtration, 5.063 kg of calcium chloride-ammonia-ammonium chloride solution is obtained.

[0050] Prepare 759.5 g of composite additive solution, including 7.59 g of sodium hexametaphosphate, accounting for 1.0%, 3.86 g of sodium tripolyphosphate, accounting for 0.5%, 1.55 g of EDTA, accounting for 0.2%, 30.9 g of sucrose, accounting for 4%, 23.18 g of stearic acid, accounting for 3%, and 692.4 g of water.

[0051] Add the prepared composite additive solution to the obtained calcium chloride-ammonia-ammonium chloride solution and mix evenly. The addition amount of the composite additive solution is 15% of the mass of the calcium chloride-ammonia-ammonium chloride solution. Control the temperature at 30 °C and introduce the purified flue gas from the power plant after dust removal, desulfurization and denitrification with a content of 10% until the solution pH = 7.5.

[0052] Centrifuge the obtained slurry with a centrifugal force of 25000 g. Continue to wash the obtained centrifugal filter cake and filter. The chloride ion content in the filter cake is 40 ppm. Put it in an oven and dry at 105 °C to constant weight. Pass through a 100-mesh sieve to obtain micron-sized calcium carbonate with uniform particle size distribution, monodispersion, and single crystal form. The average particle size is 4.2 microns, and the crystal form is a single calcite type.

[0053] Table 2 Composition content of dry-process carbide slag

[0054]

[0055] Example 3

[0056] The carbide slag is the same as in Example 2. Prepare 5 kg of 10% ammonium chloride solution, add 333.3 g of carbide slag, and stir at room temperature for 1 h for calcium extraction reaction. After filtration, 5.137 kg of calcium chloride-ammonia-ammonium chloride solution is obtained.

[0057] Prepare 506.3 g of composite additive solution, including 7.59 g of sodium hexametaphosphate, accounting for 1.0%, 3.86 g of sodium tripolyphosphate, accounting for 0.5%, 1.55 g of EDTA, accounting for 0.2%, 30.9 g of sucrose, accounting for 4%, 23.18 g of stearic acid, accounting for 3%, and 692.4 g of water.

[0058] Add the prepared composite additive solution to the obtained calcium chloride-ammonia-ammonium chloride solution, and mix evenly. The addition amount of the composite additive solution is 10% of the mass of the calcium chloride-ammonia-ammonium chloride solution. Control the temperature at 25°C, and introduce the purified flue gas from the power plant after dust removal, desulfurization and denitrification with a content of 10% until the pH of the solution reaches 7.5. Centrifuge the obtained slurry with a centrifugal force of 25000g. Continue to wash the obtained centrifugal cake, filter it. The chloride ion content in the cake is 50 ppm. Place it in an oven and dry it at 105°C until constant weight, and pass through a 100-mesh sieve to obtain micron-sized calcium carbonate with uniform particle size distribution, monodispersion, and single crystal form, with an average particle size of 5.0 microns and a single calcite crystal form.

[0059] Comparative Example 1

[0060] The raw material of carbide slag and the calcium extraction process are the same as in Example 1. Prepare 5 kg of ammonium chloride solution with a mass fraction of 10%, add 348 g of carbide slag with a moisture content of 4.2%, stir at room temperature for 1 h for calcium extraction reaction, and filter to obtain 5.15 kg of calcium chloride-ammonia-ammonium chloride solution.

[0061] Divide the above calcium chloride-ammonia-ammonium chloride solution into three equal parts, and label them as A, B, and C respectively. Add 257.5 g of a solution containing 1.29 g of sodium hexametaphosphate to solution A. Solution B is added with an additive solution lacking only EDTA, including 1.29 g of sodium hexametaphosphate, 1.03 g of sodium tripolyphosphate, 10.3 g of sucrose, 3.87 g of stearic acid, and 241 g of water. Solution C is added with an additive solution lacking stearic acid, including 1.29 g of sodium hexametaphosphate, 1.03 g of sodium tripolyphosphate, 10.3 g of sucrose, 0.26 g of EDTA, and 244.6 g of water. Mix the three solutions and the additive solutions evenly, control the temperature at 30°C, and introduce the purified flue gas from the power plant after dust removal, desulfurization and denitrification with a CO2 content of 12% until the pH of the solution reaches 8.

[0062] Centrifuge the obtained slurry with a centrifugal force of 20000g. Continue to wash the obtained centrifugal cake, filter it, wash the chloride ion content in the cake to less than 50 ppm, place it in an oven and dry it at 105°C until constant weight, and pass through a 100-mesh sieve.

[0063] The properties of the obtained calcium carbonate products are as follows:

[0064] The particle size distribution of the calcium carbonate product obtained from solution A is as Figure 5 shown, the particle size distribution is not uniform, there is agglomeration phenomenon, the particle size D50 is about 3 microns, and D90 reaches 10.8 microns

[0065] The electron microscope picture of the calcium carbonate product obtained from solution B is as Figure 6 shown, although the crystal form is spherical-like, there are obvious defects.

[0066] The average particle size of the calcium carbonate product obtained from solution C is 8.6 microns, much higher than that of other groups (less than 3 microns). It is easy to sink in water, with poor dispersibility and resulting in turbid water quality. The calcium carbonate products of other groups are suspended on the water surface and the water quality is clear after stirring.

[0067] Comparative Example 2

[0068] The carbide slag raw material and the calcium extraction process are the same as in Example 1. Prepare 5 kg of 10% ammonium chloride solution, add 348 g of carbide slag with a moisture content of 4.2%, stir at room temperature for 1 h for calcium extraction reaction, and filter to obtain 5.15 kg of calcium chloride-ammonia-ammonium chloride solution. The difference is that the composition of the compound additive prepared remains unchanged but the proportion of each component is not within the preferred range.

[0069] Prepare 772.5 g of compound additive solution, among which, sodium hexametaphosphate is 15.45 g, accounting for 2%, sodium tripolyphosphate is 0.773 g, accounting for 0.1%, EDTA is 7.725 g, accounting for 1%, sucrose is 15.45 g, accounting for 2%, stearic acid is 30.9 g, accounting for 4%, and water is 702.2 g.

[0070] Add the prepared compound additive solution to the obtained calcium chloride-ammonia-ammonium chloride solution. The addition amount of the compound additive solution is 15% of the mass of the calcium chloride-ammonia-ammonium chloride solution. Mix evenly, control the temperature at 30 °C, and introduce the purified flue gas from the power plant after dust removal, desulfurization and denitrification with a CO2 content of 12% until the solution pH = 8.

[0071] Centrifuge the obtained slurry at a centrifugal force of 20,000 g. Continue to wash the obtained centrifugal filter cake, filter, wash the chloride ion content in the filter cake to be lower than 50 ppm, put it in an oven and dry it at 105 °C to constant weight, and pass through a 100-mesh sieve.

[0072] The obtained calcium carbonate is unevenly dispersed and there is an agglomeration phenomenon. The average particle size of calcium carbonate is 10.4 microns, and the particle size is relatively large. The XRD pattern of the prepared calcium carbonate is as Figure 7 shown. There are two mixed crystal forms of calcite and vaterite in the crystal form of calcium carbonate.

Claims

1. A method for preparing micron-sized calcium carbonate based on a composite dispersant system, comprising the following steps: S1, mixing carbide slag with ammonium chloride solution to carry out calcium extraction reaction to obtain calcium chloride-ammonia-ammonium chloride solution; S2, adding the solution of the composite additive to the solution obtained in step S1, and introducing the flue gas from a power plant containing CO2 for carbonization until the pH value is 7.5-8.5; The composite additive is a composite of sodium hexametaphosphate, sodium tripolyphosphate, EDTA, sucrose and fatty acid; S3. The carbonized product obtained in step S2 is subjected to solid-liquid separation, washing and drying to obtain monodisperse micron-sized calcium carbonate.

2. The preparation method according to claim 1, characterized in that: In the solution of the composite additive, the mass percentage of each component is: Sodium hexametaphosphate 0.5%-1.5%; Sodium tripolyphosphate 0.3%-1.0%; EDTA 0.1%-0.3%; Sucrose 3%-5%; Fatty acid 1%-3%.

3. The preparation method according to claim 2, characterized in that :: In the solution of the composite additive, the mass percentage of each component is: Sodium hexametaphosphate 0.5%-1.0%; sodium tripolyphosphate 0.4%-0.5%; EDTA 0.1%-0.2%; sucrose 4%; fatty acid 1.5%-3%.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The fatty acid is any one of stearic acid, oleic acid and palmitic acid.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the carbide slag to ammonium chloride is 1:1.5-2, and the mass fraction of ammonium chloride in the ammonium chloride solution is 4%-10%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The amount of the composite additive solution added is 10%-15% of the mass of the calcium chloride-ammonia-ammonium chloride solution; The carbonization temperature is 25-35°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The CO2 volume concentration in the flue gas of the power plant is 5%-15%, and meets the following pretreatment standards: Smoke concentration ≤10mg / m 3 , SO2 concentration ≤35mg / m 3 , NOx concentration ≤50mg / m 3 , the Ringelmann blackness needs to be ≤ level 1.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The solid-liquid separation is carried out by centrifugal separation, and the centrifugal force is 15000-30000g; the chloride ion content of the product after washing is ≤200ppm.

9. micron-sized calcium carbonate prepared by the method described in any one of claims 1 to 8.

10. The micron-sized calcium carbonate according to claim 9, characterized in that: The crystal form of the micron-sized calcium carbonate is a single calcite type, the morphology is spherical, and the average particle size is 3-5 microns.

Citation Information

Cited By

  • Method for preparing high-purity vaterite based on solid waste carbonization reaction

    CN122144773A